Smartphone-supported Positive Adjustment Coping Intervention (PACI) for couples undergoing fertility treatment: a randomised controlled trial protocol - Schick, Maren; Rösner, Sabine; Germeyer, Ariane; Moessner, Markus; Bauer, Stephanie; Ditzen, Beate; Wischmann, Tewes (BMJ open, 2019)
Introduction Infertility generally counts as a profound crisis in the lives of couples and as an emotionally stressful experience. For couples undergoing fertility treatment, this is especially true of the waiting period following embryo transfer, which couples say is the most stressful period during treatment. However, at this specific phase, psychosocial counselling is not always available on the spot. The aim of this randomised controlled trial (RCT) study was to test the Positive Adjustment Coping Intervention (PACI), a low-dose, smartphone-supported psychological intervention for women and men undergoing fertility treatment. - Methods and analysis The effectiveness of PACI is tested by means of a prospective two-arm RCT. During the 14-day waiting period between oocyte puncture/oocyte thawing and pregnancy test, participants are randomly assigned to one of the two groups, and both women and men receive daily text messages on their smartphones. One group receives text messages with statements reflecting positive-adjustment coping attitudes, the other group messages containing cognitive distractions. The primary outcome of this study is the reduction of psychosocial burden during the waiting period of reproductive treatment. Furthermore, we want to assess whether there are differences between the interventions in a pre-post assessment. The secondary outcomes are information on perceived effectiveness and practicability of the intervention one month after the waiting period. - Ethics and dissemination Ethical approval has been obtained from the Ethics Committee of Heidelberg University Faculty of Medicine (S-074/2017). Study findings are planned for dissemination via peer-reviewed journal articles and at national and international conferences. - Trial registration number NCT03118219; Pre-results. - Protocol version Version 2.0 dated 18/02/2019.
Gesehen am 23.10.2019